Removal of Excess Alkali from Sodium Naphthenate Solution by Electrodialysis Using Bilayer Membranes for Subsequent Conversion to Naphthenic Acids - Aslan Achoh; Ilya Petriev; Stanislav Melnikov (Membranes, 2021)
The processing of solutions containing sodium salts of naphthenic acids (sodium naphthenate) is in high demand due to the high value of the latter. Such solutions usually include an excessive amount of alkali and a pH of around 13. Bipolar electrodialysis can convert sodium naphthenates into naphthenic acids; however, until pH 6.5, the naphthenic acids are not released from the solution. The primary process leading to a decrease in pH is the removal of excess alkali that implies that some part of electricity is wasted. In this work, we propose a technique for the surface modification of anion-exchange membranes with sulfonated polyetheretherketone, with the formation of bilayer membranes that are resistant to poisoning by the naphthenate anions. We investigated the electrochemical properties of the obtained membranes and their efficiency in a laboratory electrodialyzer. Modified membranes have better electrical conductivity, a high current efficiency for hydroxyl ions, and a low tendency to poisoning than the commercial membrane MA-41. We propose that the primary current carrier is the hydroxyl ion in both electromembrane systems with the MA-41 and MA-41M membranes. At the same time, for the modified MA-41M membrane, the concentration of hydroxyl ions in the anion-exchanger phase is higher than in the MA-41 membrane, which leads to almost five-fold higher values of the specific permeability coefficient. The MA-41M membranes are resistant to poisoning by naphthenic acids anions during at least six cycles of processing of the sodium naphthenate solution.